Cervical Spine Motion during Transfer and Stabilization Techniques. (1st January 2015) - Shrier, Ian; Boissy, Patrick; Lebel, Karina; Boulay, John; Segal, Eli; Delaney, J. Scott; Vacon, L. Charlene; Steele, Russell J.
Abstract Objectives. To compare paramedics' ability to minimize cervical spine motion during patient transfer onto a vacuum mattress with two stabilization techniques (head squeeze vs. trap squeeze) and two transfer methods (log roll with one assistant (LR2) vs. 3 assistants (LR4)). Methods. We used a crossover design to minimize bias. Each lead paramedic performed 10 LR2 transfers and 10 LR4 transfers. For each of the 10 LR2 and 10 LR4 transfers, the lead paramedic stabilized the cervical spine using the head squeeze technique five times and the trap squeeze technique five times. We randomized the order of the stabilization techniques and LR2/LR4 across lead paramedics to avoid a practice or fatigue effect with repeated trials. We measured relative cervical spine motion between the head and trunk using inertial measurement units placed on the forehead and sternum. Results. On average, total motion was 3.9° less with three assistants compared to one assistant (p = 0.0002), and 2.8° less with the trap squeeze compared to the head squeeze (p = 0.002). There was no interaction between the transfer method and stabilization technique. When examining specific motions in the six directions, the trap squeeze generally produced less lateral flexion and rotation motion but allowed more extension. Examining within paramedic differences, some paramedics were clearly more proficient with the trap squeeze technique and others were clearly more proficient with the head squeeze technique. Conclusion. Paramedics performing a log roll with three assistants created less motion compared to a log roll with only one assistant, and using the trap squeeze stabilization technique resulted in less motion than the head squeeze technique but the clinical relevance of the magnitude remains unclear. However, large individual differences suggest future paramedic training should incorporate both best evidence practice as well as recognition that there may be individual differences between paramedics.